Comprehensive studies on the stability of yogurt-type fermented soy beverages during refrigerated storage using dairy starter cultures - Ziarno, Małgorzata; Zaręba, Dorota; Ścibisz, Iwona; Kozłowska, Mariola (Frontiers in Microbiology, 2023)
Introduction This study aimed to assess the feasibility of utilizing commercially available dairy starter cultures to produce yogurt-type fermented soy beverages and evaluate the fundamental properties of the resulting products. Methods Sixteen different starter cultures commonly used in the dairy industry for producing fermented milks, such as yogurt, were employed in the study. The study investigated the acidification curves, acidification kinetics, live cell population of starter microflora during refrigerated storage, pH changes, water-holding capacity, texture analysis, carbohydrates content, and fatty acid profile of the yogurt-type fermented soy beverage. Results and Discussion The results demonstrated that the starter cultures exhibited distinct pH changes during the fermentation process, and these changes were statistically significant among the cultures. The acidification kinetics of different cultures of lactic acid bacteria showed characteristic patterns, which can be used to select the most suitable cultures for specific product production. The study also revealed that the choice of starter culture significantly influenced the starter microorganisms population in the yogurt-type fermented soy beverage. Additionally, the pH values and water-holding capacity of the beverages were affected by both the starter cultures and the duration of refrigerated storage. Texture analysis indicated that storage time had a significant impact on hardness and adhesiveness, with stabilization of these parameters observed after 7–21 days of storage. Furthermore, the fermentation process resulted in changes in the carbohydrate content of the soy beverages, which varied depending on the starter culture used.